PERSEPSI MASYARAKAT DALAM PENGELOLAAN SMART MOBILITY TRANSPORTASI PUBLIK - Hafifah Humaida; Aldri Frinaldi (Jurnal Teori dan Riset Administrasi Publik, 2023)
Smart Mobility is one of the components in the development of a smart city, related to mobility or community movement which is often associated with public transportation. Trans Padang is city transportation that is managed directly by the Padang Sejahtera Mandiri Regional Public Company. This transportation is currently carrying out an update that targets the realization of the Padang City strategic plan 2024. However, it is certainly necessary to see the public's perception of the management of transportation operations, so that the renewal is carried out according to the needs of the community as the target user of the service. This research is descriptive qualitative research which is then processed using the Manual Data Analysis Procedure method. The coding was carried out in the stages of open coding, axial coding and selective coding which were then used as memos to visualize the research data. There were obstacles felt by the community in service, such as the absence of a scheduled departure and arrival of buses, buses with loads exceeding capacity, lack of clarity on the names of bus stops, and poor interiors. This departure schedule can be overcome by implementing a smart transport system that can produce real-time information system products, which will make it easier for the public to access bus departure and arrival information. By doing this research, it is found the real problems that occur in the field can be used as a reference in updating and improving the quality of Trans Padang services.